Lucjan Rydel i piękna książka - Bąbiak , Grzegorz P. (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
Artistic activity at the turn of the 19th and 20th centuries resulted not only in the development of literature and art, but also functional art and crafts, e.g. graphics and book decoration. Apart from artistic press, it was clearly visible in the phenomenon of the so-called beautiful book. The most distinguished artists of that period: Stanisław Wyspiański, Jan Bukowski, Antoni Procajłowicz - designed covers, vignettes and decorations of the best-known literary works. Lucjan Rydel, who found himself among those artists, was a friend of Wyspiański and cooperated with him, which meant that their first joint works heralded the discussed phenomenon at the Vistula River. This big event was the publication of Rydel’s translation of Iliada with the pictures and illustrations by Wyspiański, who also decorated Rydels’ volumes of poetry, using floral motifs, which were typical in his later work. Also other artists in their ornaments have tried to refer to the motifs which were dominant in Rydel’s works. Thanks to this practice, some editions of dramas (1902, designed by A. Procajłowicz) and Bajka o Kasi i królewiczu (1904, designed by S. Dębicki) should be regarded as the most renowned works of the ‘beautiful book’ trend, not only in Poland, but also in East-Central Europe. This paper focuses on the most representative ‘beautiful books’, based on Lucjan Rydel’s works from the period 1896-1911.